Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Pelanggan Beberapa Generasi Di Kedai Kopi “Simple Group” Surabaya Dan Gresik - I Gede Wiyasa MS (Journal of Management and Creative Business, 2023)
Service quality is a service that focuses on meeting needs and requirements, as well as on timeliness to meet customer expectations. The purpose of this research is to prove that service quality affects customer satisfaction at the "Simple Group" café in Surabaya and Gresik. This research was conducted by census or purposive sampling on customers who visited more than once a month with 105 respondents as customers. Data collection techniques are interviews, observations, and questionnaires. This study proves and analyzes the effect of service quality on satisfaction at the “Simple Group” coffee shop in Surabaya and Gresik. The results of the analysis can be concluded that customer satisfaction is largely determined by the quality of service that deals directly with customers. Where in this case satisfaction when interacting is that customers get comfortable and good service from employees of the "Simple Group" coffee shop in Surabaya and Gresik